Evaluation of Small Molecular Polypeptides from the Mantle of Pinctada Martensii on Promoting Skin Wound Healing in Mice - Yang, Faming (Molecules, 2019)
Skin wound healing, especially chronic wound healing, is a common challenging clinical problem. It is urgent to broaden the sources of bioactive substances that can safely and efficiently promote skin wound healing. This study aimed to observe the effects of small molecular peptides (SMPs) of the mantle of Pinctada martensii on wound healing. After physicochemical analysis of amino acids and mass spectrometry of SMPs, the effect of SMPs on promoting healing was studied through a whole cortex wound model on the back of mice for 18 consecutive days. The results showed that SMPs consisted of polypeptides with a molecular weight of 302.17–2936.43 Da. The content of polypeptides containing 2–15 amino acids accounted for 73.87%, and the hydrophobic amino acids accounted for 56.51%. Results of in vitro experimentation showed that SMPs possess a procoagulant effect, but no antibacterial activity. Results of in vivo experiments indicated that SMPs inhibit inflammatory response by secretion of anti-inflammatory factor IL-10 during the inflammatory phase; during the proliferative phase, SMPs promote the proliferation of fibroblasts and keratinocytes. The secretion of transforming growth factor-β1 and cyclin D1 accelerates the epithelialization and contraction of wounds. In the proliferative phase, SMPs effectively promote collagen deposition and partially inhibit superficial scar hyperplasia. These results show that SMPs promotes dermal wound healing in mice and have a tremendous potential for development and utilization in skin wound healing.